Sulphur supply to peas (Pisum sativum L.) influences symbiotic N2 fixation - H.W. Scherer; S. Pacyna; N. Manthey; M. Schulz (Plant, Soil and Environment, 2006)
In a pot experiment (culture substrate: perlite with a granulometric composition 0-3 mm) with peas (Pisum sativum L.) we studied the influence of sulphur supply on S and N concentrations, yield formation, symbiotic N2 fixation and available amounts of glucose and sucrose. Under S deficiency conditions S and N concentrations as well as the amounts of glucose and sucrose in shoots and nodules were significantly reduced. We assume that the reduced amounts of available photosynthate with suboptimal S supply could become limiting to energy production and as carbon skeletons for ammonia assimilation, and therefore cause a lower N2 fixation and a reduced yield formation.